Threefold-Hierarchical Transport of Highly Concentrated Aqueous Electrolyte Mediated by Environment-Reconstructed Ion Correlation Networks - Wang, Qiang; Tian, Di; Qu, Zhiguo (Nano-Micro Letters, 2026)
Highly concentrated aqueous electrolytes (HCAEs) offer superior energy density and stability in energy conversion and storage than their diluted counterparts, attributed to enhanced ion transport and correlated ion structures. However, their underlying structure–transport relationships remain poorly understood in wide-temperature and nanoconfinement environments. This study captures electrolyte structure and transport fingerprints shaped by environmental factors, by combining experimental characterization with first-principles molecular simulations at sub-nanometer resolution. It is revealed that ultrahigh concentration changes electrolyte electronic states and forms ion correlation networks with extensive aggregates. These alterations reduce free water content and hydrogen bond network connectivity, resulting in notable deviation from the Nernst–Einstein (NE)-predicted conductivity. This deviation is thermal-alleviated by weakening ion correlations. Nanoconfined interfaces create oscillatory-decaying distribution and heterogeneous orientation in HCAE constituents, resulting in redrawn ion correlation networks and localized NE deviations. Such transport behaviors are further modulated by synergistic thermal-interfacial constraints. Taking NE deviations as descriptors, HCAE transport, mediated by environment-reconstructed ion correlation networks, is then summarized to present threefold-hierarchical variations due to ion concentration, thermal effect, and confinement extent. This threefold-hierarchical framework is transferable among diverse electrolytes, offering a localized insight for electrolyte evaluation in electrochemical energy devices. Highlights: 1 Transport fingerprints of aqueous electrolytes are captured to be mediated by environment-reconstructed ion correlation networks. 2 Taking the Nernst–Einstein deviations as descriptors, electrolyte transport presents threefold-hierarchical variations due to salt concentration, thermal effect, and nanoconfined interface. 3 This threefold-hierarchical framework is transferable among diverse electrolytes, offering a localized insight for electrolyte evaluation in electrochemical energy devices.